(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The present research studies the predatory spiders which are found in the silk nests of Fall Webworm infesting Acer negundo L., a tree of North American origin introduced in Europe about three centuries ago. The data are compared with the ones obtained from the previous research regarding the spider population of the moth nests infesting Morus alba L. Since Acer negundo L. and Morus alba L. are considered as target-trees of the phytophagous in the Po valley. Differences between the two populations came out both as regard the number of species gathered and determined (6 on Acer negundo and 10 on Morus alba) and as to other parameters taken into consideration. However the predation trials carried out in the laboratory have pointed out a certain good action of control from spiders towards Fall Webworm.